The Concept of Application of Integrity Values in The Management of Zakat Institutions - Muhsin Nor Paizin (Garuda Prestasi Nusantara Consulting, 2021)
The purpose of this paper is to explore and provide insights to see how the value of integrity can be applied among zakat institutions so that zakat officers can perform their duties honestly and sincerely only because of Allah SWT. This research also tries to suggest improve the existing zakat management system so that it is more efficient and systematic, and to make the zakat institution as a place to produce employees who uphold the noble values among the local community. This research adopts qualitative research approach using the holy Al-Qur’an as a primary source and hadith of the Rasulullah SAW supported by the anecdotes of his companions as a secondary source and prior literature. While performing the duties entrusted to him or her, whether while holding a position in the government service, private, statutory body or self-employed, many challenges will be faced especially those involving integrity. Therefore, in order to address these challenges, it is definitely necessary to know and recognize the characteristics of reprehensible mazmumah which is a stumbling block to the implementation of integrity.